Keragaman Jenis Tanaman Pada Dua Sistem Pertanian di Pegunungan Arfak Papua Barat - Purbokurniawan; Siti Hajar Kubangun; Alce Ilona Noya; Yanuarius Anouw (Cassowary, 2021)
The geographical of Pegunungan Arfak Regency was at 1200 - 2300 meters above sea level, has a mountainous topography, potential for the development of economic highlands crops. The aim this research was to see the diversity of cultivated plant by Arfak people at Arfak mountainous in their field and yard farming system. These studies were conducted at 2 Districts: 1) Anggi: Testega, Bamaha and Kostera Village; 2) Anggi Gida at Tuabiam Village of Pegunungan Arfak Regency. The data collected by survey technique. The results showed there were a diversity of cultivated plants at two different farming system by Arfak people. There were 30 cultivated plants in four villages; consisted of 9 types of carbohydrate plants, 6 types of vegetable plants, 5 types of fruit plants, 8 types of spice plants and 2 types of sweeteners and fresheners. There were 11 crop in fields and 29 crop in yard farming system, respectively.